2019
DOI: 10.1609/aaai.v33i01.33019528
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrapping Conversational Agents with Weak Supervision

Abstract: Many conversational agents in the market today follow a standard bot development framework which requires training intent classifiers to recognize user input. The need to create a proper set of training examples is often the bottleneck in the development process. In many occasions agent developers have access to historical chat logs that can provide a good quantity as well as coverage of training examples. However, the cost of labeling them with tens to hundreds of intents often prohibits taking full advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Finally, our work improves dialogue quality by utilizing larger datasets with noisier labels than traditional supervision. Other applications of weak supervision to dialogue (Mallinar et al, 2019) and relation extraction have observed similar results (Bunescu and Mooney, 2007;Hancock et al, 2018;Ratner et al, 2017).…”
Section: Related Worksupporting
confidence: 61%
“…Finally, our work improves dialogue quality by utilizing larger datasets with noisier labels than traditional supervision. Other applications of weak supervision to dialogue (Mallinar et al, 2019) and relation extraction have observed similar results (Bunescu and Mooney, 2007;Hancock et al, 2018;Ratner et al, 2017).…”
Section: Related Worksupporting
confidence: 61%
“…Recent works point to two directions to build quality intent models. Re-using available conversation log, to bootstrap intent model building process (Mallinar et al, 2018;Goyal et al, 2018;Shi et al, 2018;Liu et al, 2007). The other is to allow domain experts to build an intent model by working on the model definition, labeling, and evaluation through user interfaces (Williams et al, 2015).…”
Section: Related Workmentioning
confidence: 99%
“…Gathering good quality labeled data for any machine learning process is expensive. There have been significant efforts to reduce labeling effort; including work on clustering(Cheung and Li, 2012;Xu et al, 2017;Perkins and Yang, 2019), semi-supervised learning (Chapelle et al, 2010), active learning (Settles, 2012), transfer learning (Goyal et al, 2018) and also recently proposed data programming frameworks (Ratner et al, 2017;Mallinar et al, 2018). Semi-supervised, Transfer learning and active learning require seed training data for processing.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a lot of work regarding semisupervision, for both image, video, and text classification (Li et al, 2019;Mallinar et al, 2019). Wang et al (2009), for example, applied semisupervised learning algorithms for video annotation.…”
Section: Related Workmentioning
confidence: 99%